A biographical portrait of Dr. Eduardo Cáceres-Graziani (1913 - 2010) - Cotrina Díaz, Manuel (2010)
We do not have enough space for describing all the achievements of Professor Eduardo Caceres-Graziani and his immense love for mankind. He was a brilliant researcher and academician. He also was a model for every colleague working with him. We are committed to continue with his legacy full of humbleness and abnegation.